Long-Term Real-World Outcomes of Tenofovir Alafenamide in Chronic Hepatitis B: Detailed Analysis of Treatment-Naive and Experienced Patients - Yu-Xuan Song; Guang-Jun Song; Hui Ma; Bo Feng; Yan-Di Xie (The Korean Journal of Gastroenterology)
Background/Aims: This study assessed the long-term efficacy and safety of tenofovir alafenamide (TAF) in real-world settings. Methods: Patients who were candidates for TAF treatment and were followed up at 12-week intervals over 192 weeks were enrolled in this study. Results: One hundred and forty-four patients (50 treatment-naive and 94 treatment-experienced) were included in this study. The cumulative incidence rates of cirrhosis and hepatocellular carcinoma at 192 weeks were 3.9% and 0.7%, respectively. In treatment- naive patients, the rates of a virological response, HBeAg conversion, and HBsAg loss at 192 weeks were 100%, 33.3%, and 2%, respectively. The treatment-naive patients exhibited higher baseline HBsAg levels than the treatment-experienced patients (4.31 log10IU/mL vs. 3.97 log10IU/mL). A significant decrease in the HBsAg levels from the baseline was observed at 144 and 192 weeks in the treatment-naive patients (p=0.01). The baseline body mass index (BMI) <25 kg/m2 (p=0.02) and HBsAg <3.3 log10IU/mL (p=0.04) were identified as predictive factors for a decrease in HBsAg ≥0.5 log10IU/mL at 48 weeks. The eGFR levels were consistently lower in the treatment-experienced patients throughout the study. Although the treatment-naive patients showed no abnormal increases in urinary URBP, the treatment-experienced patients showed elevated urinary β2MG and NAG levels at the baseline, which decreased over the treatment course. The total cholesterol, triglyceride, and low-density lipoprotein levels were similar in both groups. Conclusions: Prolonging the TAF treatment duration enhances the virological response rate. The decline in HBsAg levels was more significant in the treatment-naive patients than in the treatment-experienced patients. The baseline BMI <25 kg/m2 and HBsAg <3.3 log10IU/mL were predictive factors for a significant decline in HBsAg at 48 weeks. TAF has high renal safety and no significant impact on lipid levels.